Prothrombotic changes in patients with COVID‐19 are associated with disease severity and mortality - von Meijenfeldt, Fien A.; Havervall, Sebastian; Adelmeijer, Jelle; Lundström, Annika; Rudberg, Ann‐Sofie; Magnusson, Maria; Mackman, Nigel; Thalin, Charlotte; Lisman, Ton (Research and practice in thrombosis and haemostasis, 2021)
Patients with severe coronavirus disease 2019 (COVID‐19) are at significant risk of thrombotic complications. However, their prothrombotic state is incompletely understood. Therefore, we measured in vivo activation markers of hemostasis, plasma levels of hemostatic proteins, and functional assays of coagulation and fibrinolysis in plasma from patients with COVID‐19 and determined their association with disease severity and 30‐day mortality. We included 102 patients with COVID‐19 receiving various levels of respiratory support admitted to general wards, intermediate units, or intensive care units and collected plasma samples shortly after hospital admission. Patients with COVID‐19 with higher respiratory support had increased in vivo activation of coagulation and fibrinolysis, as reflected by higher plasma levels of d‐dimer, thrombin‐antithrombin, and plasmin‐antiplasmin complexes as compared to patients with no to minimal respiratory support and healthy controls. Moreover, the patients with COVID‐19 with higher respiratory support exhibited substantial ex vivo thrombin generation and lower ex vivo fibrinolytic capacity, despite higher doses of anticoagulant therapy compared to less severely ill patients. Fibrinogen, factor VIII, and von Willebrand factor levels increased, and ADAMTS13 levels decreased with increasing respiratory support in patients with COVID‐19. Low platelet count; low levels of prothrombin, antithrombin, and ADAMTS13; and high levels of von Willebrand factor were associated with short‐term mortality. Severe COVID‐19 is associated with prothrombotic changes with increased in vivo activation of coagulation and fibrinolysis, despite anticoagulant therapy.